Bulgarian Capitalisms - Prodanov, Vasil (Research Papers, 2015)
The subject of this study are the two main stages of the Bulgarian capitalisms from the Liberation to the present day - 66 years of the first Bulgarian capitalism between 1878 and 1944. There are 45 years of interruption and then came the second Bulgarian capitalism during the next 25 years.At the beginning of the study the main characteristics of the first Bulgarian capitalism are reconstructed. This capitalism occurred in a backward country, a periphery of the Western capitalism. The scarcity of resources and the delayed development, and also the geopolitical situation of the battle for hegemony of the Great Forces in two world wars defined its peculiarities, and ultimately his inability to realize its modernization tasks.The discourse of “transition to democracy and market economy” acquired a hegemonic status after the end of the state socialism. However behind this discourse a reality of economic, political and ideological restoration of capitalism is hidden. The first Bulgarian capitalism, especially after 1934, is based on a strong government while the second Bulgarian capitalism is born in a time of a global neoliberal wave and largely destroyed the country and dramatically reduces the effectiveness of institutions.There are three main characteristics of the second Bulgarian capitalism, analyzed in this study – they are connected with comprador elites, kleptocracy, peripheral development. This leads to its strong destructiveness, which specifically is analyzed in this study.